Efficacy of corticosteroids for cancer-related fatigue: A pilot randomized placebo-controlled trial of advanced cancer patients. Issue 5 (October 2015) - Eguchi, Kenji; Honda, Michitaka; Kataoka, Tatusji; Mukouyama, Taketo; Tsuneto, Satoru; Sakamoto, Junichi; Oba, Koji; Saji, Shigetoyo
Abstract: Objective: Cancer-related fatigue (CRF) is a common and one of the most important issues in palliative medicine, and it has been demonstrated to have a significant impact on patient quality of life (QoL). The present pilot randomized controlled study evaluated the efficacy and toxicity of methylprednisolone (MP) for CRF in advanced cancer patients. Method: Our study was planned as a randomized, double-blind, multicenter, placebo-controlled trial. Patients were randomly assigned to an MP group, who received 32 mg/day of MP orally for 7 days, and a placebo group. The primary endpoint was an improvement in visual analog scale (VAS) score for fatigue from baseline to day 7. The secondary endpoints were improvements in appetite loss and QoL as well as evaluating the safety of corticosteroids as palliative therapy. Results: It was not possible to complete patient registration. In total, 35 patients were randomly assigned to an MP group ( n = 18) and a placebo group ( n = 17). The mean changes in VAS score for fatigue were –9.06 in the placebo group and –1.56 in the MP group, and for appetite loss –6.44 in the placebo group and –8.06 in the MP group. In addition, there was no evidence that methylprednisolone improved appetite loss or QoL compared to placebo. The incidence of adverse effects was not greater in the MP group. Significant of Result: We conclude that our sample size was too small to prove the efficacy of methylprednisolone in improving fatigue. Our results were reported as a pilot study performed to support a subsequent larger trial.